Analysis of Strategies for Enhancing Altruistic Attitudes Based on the Guidance of Hadith - Asnawiyah, Asnawiyah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2021)
This article delves into the intricate realm of altruistic hadiths within the Islamic tradition, shedding light on their ethical significance and profound implications for contemporary society. Altruism, as a fundamental virtue in Islam, manifests through various prophetic traditions encapsulated in hadith literature. Employing a qualitative analysis approach, this study examines the contextual nuances and moral imperatives embedded within altruistic hadiths, elucidating their relevance to modern ethical discourse. The research synthesizes classical Islamic scholarship with contemporary ethical theory to elucidate the multifaceted nature of altruistic hadiths. By dissecting the linguistic intricacies and historical contexts of these traditions, the article unveils their underlying principles and ethical imperatives. Moreover, it explores the socio-cultural dynamics that shaped the formulation and transmission of altruistic hadiths, providing valuable insights into the ethical framework of early Islamic societies. Furthermore, the article investigates the practical applications of altruistic hadiths in addressing contemporary moral challenges and fostering communal well-being. It highlights the role of altruism as a catalyst for social cohesion, compassion, and solidarity, thereby enriching the fabric of Islamic ethics in the contemporary world. Additionally, it underscores the imperative of interpreting altruistic hadiths in light of evolving social realities while preserving their ethical integrity and spiritual resonance. In conclusion, this article underscores the enduring relevance and ethical profundity of altruistic hadiths, urging scholars and practitioners alike to engage with these traditions critically and compassionately. By embracing the ethical imperatives embedded within these prophetic teachings, individuals and communities can strive towards a more just, compassionate, and altruistic society rooted in the timeless wisdom of Islamic tradition.